PELATIHAN PEMROGRAMAN KOMPUTER DENGAN PENDEKATAN INOVATIF MELALUI INTEGRASI ENGLISH FOR SPECIFIC PURPOSES (ESP) PADA MAHASISWA SARJANA TERAPAN MANAJEMEN INFORMASI KESEHATAN STIKES MITRA HUSADA KARANGANYAR - Trismianto Asmo Sutrisno; Erna Adita Kusumawati (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Computer programming is one of compulsory courses in the Applied Health Information Management Study Program at STIKes Mitra Husada Karanganyar. The computer programming course consists of Basic Programming and Web Programming. The skills gained from computer programming will greatly support the careers of graduates because medical recorders or coders are required to face an all-electronic work environment, particularly in relation to Electronic Medical Records (EMR). The digital era requires health information management graduates to not only master aspects of health information management itself but also have adequate programming skills. In addition, English language skills, especially in technical contexts (English for Specific Purposes), are crucial for accessing the latest resources, documentation, and trends in the world of global health information technology. This community service activity aimed to improve the computer programming competency of Applied Health Information Management students at STIKes Mitra Husada Karanganyar by using an innovative approach through the integration of English for Specific Purposes (ESP). This issue related to the challenges usually faced by health information management students toward the understanding of complex programming concepts and technical jargon in English. This was due to a lack of mastery of English vocabulary, particularly technical terms related to programming languages and instructions that use English. Computer programming training with an innovative approach through the integration of English for Specific Purposes (ESP) for Applied Health Information Management students at STIKEs Mitra Husada Karanganyar was conducted through several methods, such as lectures, discussions, and practical exercises. This allowed students to directly apply their acquired English language skills (ESP) to computer programming commands.